Laser treatment for tracheobronchial tumours: local or general anaesthesia?. Issue 9 (September 1987) - George, P J; Garrett, C P; Nixon, C; Hetzel, M R; Nanson, E M; Millard, F J
Abstract : Ninety seven patients with tracheobronchial tumours have been treated with the neodymium yttrium-aluminium-garnet (Nd YAG) laser over a period of 33 months. Fifty one of these patients were treated under local anaesthesia and 46 under general anaesthesia. The results obtained with the two methods have been compared retrospectively. The numbers of patients responding to treatment, the magnitude of the response, and the duration of palliation were similar in the two groups; significantly more treatment sessions, however, were required during each course of treatment under local anaesthesia. This advantage of general anaesthesia was thought to arise from the ability to continue treatment for longer and with greater efficiency. The use of the rigid bronchoscope with jet ventilation under general anaesthesia was also thought to provide better control of the airway and to allow more efficient clearance of blood and mucus. Two operative deaths occurred under local anaesthesia, when bleeding led to asphyxiation, but none have occurred under general anaesthesia. Treatment under general anaesthesia is not, however, without risk and is potentially hazardous in patients with severe chronic hypoxic lung disease.